The development of love literature and Adoring in medieval culture Arabic classical - Rayyan, Mahmoud Jamal (Arab Journal for Sciences and Research Publishing, 2022)
This article comes to look for love poetry and literature, as a literary genre that has its beginning and continuity; and through exposure to several fundamental themes related to this literary jener. So that we deal with love as an idea and as a behavior, and the relationship of love to love through literary studies, stories of love, and above all we will see the relationship of love literature and poetry to the theory of love according to a historical hierarchy; the roots from the first Islamic times, and then extend to centuries late, according to what researchers and orientalists have dealt with about the theory and literature of love. Its importance comes in the need to reveal the relationship of theory with literature and poetry, in their dialectical attachment and the themes covered, and we have shown that there is a relationship between love literature and theory in the period we have chosen specifically.